Evaluation of the Lung Immune Prognostic Index in Non-Small Cell Lung Cancer Patients Treated With Systemic Therapy: A Retrospective Study and Meta-Analysis - Huang, Litang; Han, Hedong; Zhou, Li; Chen, Xi; Xu, Qiuli; Xie, Jingyuan; Zhan, Ping; Chen, Si; Lv, Tangfeng; Song, Yong (Frontiers in Oncology, 2021)
Abstract The lung immune prognostic index (LIPI) has been shown to be an important prognostic marker for various tumors. However, the prognostic value of LIPI among non-small cell lung cancer (NSCLC) patients treated with systemic therapy remains controversial. We aimed to evaluate survival status according to LIPI among NSCLC patients receiving different forms of systemic therapy at our institution. We also performed a meta-analysis of articles from PubMed and Embase to illustrate this question. For our cohort, we found that good LIPI was associated with better overall survival (OS) among 91 patients on immunotherapy 329 patients on targeted therapy and 570 patients on chemotherapy, respectively. For the meta-analysis, a total of eight studies with 8,721 patients were included. Pooled results showed that a higher LIPI (those with 1 or 2 factors) was associated with poor overall PFS (hazard ratio [HR], 1.57; 95% confidence interval [CI], 1.451.71) and OS (HR, 2.01; 95% CI, 1.752.31). Subgroup analyses showed that a higher LIPI was related to poor survival among patients prescribed different systemic therapies: immunotherapy (OS HR, 2.50; 95% CI, 1.99–3.13; PFS HR, 1.77; 95% CI, 1.56–2.01), chemotherapy (OS HR, 1.58; 95% CI, 1.34–1.86; PFS HR, 1.38; 95% CI, 1.23–1.55;), and targeted therapy (OS HR; 2.15, 95% CI, 1.57–2.96; PFS HR, 1.60; 95% CI, 1.25–2.06). The study shows that the LIPI is a clinically significant prognostic factor for NSCLC patients receiving systemic therapy.